Fundamental Challenges to Global Peace and Security
XVII, 331 p. 11 illus., 6 illus. in color.
Keywords: This book challenges the current thinking and strategies in the field of global peace and security. It is clear that current global public and private institutions are inadequate for the challenges we face today. These challenges cut across borders and require a more coordinated and concerted effort to find workable solutions. This book therefore begins with the question of global leadership and works its way back to the interconnected dynamics of global modernity and conflict. It is divided into four parts, each addressing a fundamental challenge to global peace and security. By exploring how we break out of the current framework, in which we understand global activities and the distribution of resources, and this book provides new ways of understanding the material, cultural, political, and spiritual relations that form the basis of international society. Hoda Mahmoudi is Research Professor and Chair, The Bahá’í Chair for World Peace, Universityof Maryland, USA. Michael Allen is Chair and Professor of Political Science on the Harvey Wexler Chair in Political Science, and Co-Director of International Studies, Bryn Mawr College, USA. Kate Seaman is Assistant Director, The Bahá’í Chair for World Peace, University of Maryland, USA. .